EXTENDED 3β-ALKYL STERANES AND 3-ALKYL TRIAROMATIC STEROIDS IN CRUDE OILS AND ROCK EXTRACTS - Dahl J.; Moldowan J.M.; Summons R.E.; McCaffrey M.A.; Lipton P.; Watt D.S.; Hope J.M. (My University, 1995)
In oils and Precambrian- to Miocene-age source rocks from varying depositional environments, we have conclusively identified several novel 3-alkyl sterane and triaromatic steroid series, including (1) 3β-n-pentyl steranes, (2) 3β-isopentyl steranes, (3) 3β-n-hexyl steranes, (4) 3β-n-heptyl steranes, (5) 3,4-dimethyl steranes, (6) 3β-butyl,4-methyl steranes, (7) triaromatic 3-n-pentyl steroids, and (8) triaromatic 3-isopentyl steroids. We have also tentatively identified additional homologs with 3-alkyl substituents as large as C11. The relative abundances of these compounds vary substantially between samples, as indicated by (1) the ratio of 3β-n-pentyl steranes to 3β-isopentyl steranes and (2) the ratio of 3-n-pentyl triaromatic steroids to 3-isopentyl triaromatic steroids. These data suggest possible utility for these parameters as tools for oil-source rock correlations and reconstruction of depositional environments. Although no 3-alkyl steroid natural products are currently known, several lines of evidence suggest that 3β-alkyl steroids result from bacterial side-chain additions to diagenetic Δ2-sterenes.
Keywords: Miocene; Precambrian; Cenozoic::Neogene::Miocene; Precambrian; Докембрий; Кайнозой::Неоген::Миоцен